Advances and future directions in betalain metabolic engineering. Issue 4 (11th July 2019) - Polturak, Guy; Aharoni, Asaph
Abstract : Summary: Betalains are nitrogenous red and yellow pigments found in a single order of plants, the Caryophyllales, and in some higher fungi. They are responsible for the colors observed in many ornamental plants, as well as in various food products, where they are used as natural colorants. Their nutritional properties and attractive colors make them an appealing target for metabolic engineering. This is further heightened by the limited availability of natural betalain sources, arising from their relative scarcity in the plant kingdom, particularly in edible plants. Recent progress in decoding their biosynthetic pathway has facilitated stable heterologous production of betalains in several plant and microbial systems. Here, we provide a brief review of recent advances and discuss current approaches and possible future directions in betalain metabolic engineering, including expanding the chemical diversity of betalains and increasing their yield, exploring new host organisms for their heterologous production, and engineering their secretion from the cell.